A quasi-3D theory for vibration and buckling of functionally graded sandwich beams. (January 2015) - Vo, Thuc P.; Thai, Huu-Tai; Nguyen, Trung-Kien; Inam, Fawad; Lee, Jaehong
Abstract: This paper presents a finite element model for free vibration and buckling analyses of functionally graded (FG) sandwich beams by using a quasi-3D theory in which both shear deformation and thickness stretching effects are included. Sandwich beams with FG skins-homogeneous core and homogeneous skins-FG core are considered. By using the Hamilton's principle, governing equations of motion for coupled axial–shear–flexural–stretching response are derived. The resulting coupling is referred to as fourfold coupled vibration and buckling. Numerical examples are carried out to investigate the thickness stretching effect on natural frequencies and critical buckling loads as well as mode shapes of sandwich beams for various power-law indexes, skin–core–skin thickness ratios and boundary conditions.